ANALISIS MANAJEMEN RANTAI PASOK PRODUK OTAK-OTAK PADA UMKM DI KIJANG - Dwila Sempi Yusiani; Meylia Vivi Putri (LPPM Universitas Ibnu Sina, 2025)
Kijang, located in Bintan Regency, Riau Islands Province, is known as one of the main production centers of otak-otak made from fresh marine fish, playing an important role in the local economy through small and medium enterprises (SMEs). Nevertheless, its supply chain faces various challenges, such as fluctuations in supply and prices of raw materials, limited processing technology, and dependence on traditional marketing methods. This study aims to analyze the influence of supply chain management on the business performance of otak-otak SMEs in Kijang. The method used is descriptive qualitative, with data collected through structured interviews, direct observation, questionnaires, and literature review. The results show that the supply chain consists of fresh fish procurement from local fishermen, semi-traditional production processes, distribution through direct sales or retailers, and marketing via offline outlets and limited online platforms. The main problems include price increases during the off-season, inconsistent product quality, and suboptimal use of digital marketing. However, there are development opportunities through supplier diversification, modernization of production equipment, implementation of standardized quality control procedures, and integration of digital marketing systems. These strategies are expected to improve operational efficiency, maintain product quality, expand market reach, and strengthen competitiveness in both local and regional markets